Antecedents of primary school teachers' need-supportive and need-thwarting styles in physical education. (November 2021) - Escriva-Boulley, Géraldine; Haerens, Leen; Tessier, Damien; Sarrazin, Philippe
It is widely acknowledged that teachers' (de)motivating style (what they say, do and how they act) affects students' learning. Understanding what leads teachers to adopt a (de)motivating style is necessary to develop effective training programmes. The current study aimed to identify antecedents of teachers' motivating (i.e. need-supportive) and demotivating (i.e. need-thwarting) styles by (a) examining the relationships between five types of pressures and these styles and (b) investigating the mediating role of motivation. A total of 509 generalist primary school teachers completed a questionnaire about their perceived styles, perceived pressures from above (i.e. time constraints, pressure to display authority), below (i.e. perceptions of students' disengagement) and within (i.e. beliefs about the effectiveness of rewards, and the adherence to entity theory), and their autonomous and controlled motivations to teach physical education. Structural equation modelling showed that a need-supportive style was negatively predicted by students' disengagement and teachers' adherence to entity theory, and this relation was fully mediated by autonomous motivation. A need-thwarting style was positively predicted by pressure to display authority and beliefs about the effectiveness of rewards. Results showed that when pressures from below and from within are reduced, teachers adopt a more need-supportive style, because they are more likely to enjoy and value teaching. Conversely, when pressures from above and from within are prevalent, teachers are more likely to adopt a need-thwarting style. This study identified the pressures to be targeted when developing interventions which aim to modify teachers' (de)motivating styles which in turn could impact students' motivation and behaviours.